1982
DOI: 10.1056/nejm198201073060101
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of Primary Biliary Cirrhosis after Liver Transplantation

Abstract: Three patients who had undergone orthrotopic liver transplantation for primary biliary cirrhosis and were being maintained on immunosuppressive therapy were investigated 31/2 to 41/2 years later because of the redevelopment of pruritus and mild jaundice. In one patient pigmentation was again evident, and all three had a rise in the titer of serum mitochondrial antibody after an initial fall. Liver histology showed features of primary biliary cirrhosis with non-suppurative destructive cholangitis, lymphoid aggr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
101
0
3

Year Published

1988
1988
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 243 publications
(106 citation statements)
references
References 7 publications
2
101
0
3
Order By: Relevance
“…We can only state that we were unable to diagnose the disease using the criteria offered by Neuberger et a1. (10). The reasons we were unable to diagnose recurrent disease with certainty included the different histopathologic appearance of PBC and chronic rejection, the lack of correlation of AMA levels with liver dysfunction and/or hepatic pathology and our ignorance of the effect of cyclosporin therapy on the histopathology of PBC.…”
Section: Pathologic Comparison Of Native Hepatectomies With Pbc and Fmentioning
confidence: 98%
See 3 more Smart Citations
“…We can only state that we were unable to diagnose the disease using the criteria offered by Neuberger et a1. (10). The reasons we were unable to diagnose recurrent disease with certainty included the different histopathologic appearance of PBC and chronic rejection, the lack of correlation of AMA levels with liver dysfunction and/or hepatic pathology and our ignorance of the effect of cyclosporin therapy on the histopathology of PBC.…”
Section: Pathologic Comparison Of Native Hepatectomies With Pbc and Fmentioning
confidence: 98%
“…The difficulty of using pathologic observations for the diagnosis of PBC after transplantation is underscored by the experience at Cambridge (10). Since their original report, the Cambridge group has identified patients who developed a PBC-like syndrome (clinically and pathologically) after transplantation but did not have the disease originally, nor did they convert to AMA positivity (24).…”
Section: Pathologic Comparison Of Native Hepatectomies With Pbc and Fmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial report of recurrence of PBC in three patients by Neuberger et al 15 was not confirmed in the Pittsburgh experience. 16 Recurrence of the disease, using the criteria described by Neuberger et al, 15 was not found by Demetris et al 17 in a recent pathologic review of graft specimens obtained from 106 patients with PBC.…”
Section: The Issue Of Recurrence Of the Disease After Transplantationmentioning
confidence: 89%